State of emergency an economic analysis - Bjørnskov, Christian (Cambridge University Press, 2024)
Nine out of ten constitutions contain explicit emergency provisions. During the pandemic, half of the governments with such constitutions has made use of these provisions by declaring a state of emergency. State of Emergency is the first book to analyse the factors that lead to such provisions being included in newly drafted constitutions. It explores their use - as well as their misuse - and explains the effects that using emergency provisions has. Declaring a state of emergency is particularly challenging in federally constituted states as it endangers the balance of powers between the federal level and the states. This book, therefore, pays special attention to this topic. Focusing on two of the most important recent cases relating to emergency provisions: the Covid-19 pandemic and acts of terrorism, this book uses numerous examples to analyse emergency provisions with a rigorous empirical approach.